2018
DOI: 10.1186/s12985-018-0927-5
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B infection and preeclampsia among pregnant Sudanese women

Abstract: BackgroundPrevious published studies have reported conflicting results of association between hepatitis B virus (HBV) infection and preeclampsia. There was no published data on HBV and preeclampsia in Africa including Sudan. The aim of the present study was to investigate the association between HBsAg seropositivity and preeclampsia.MethodsA case –controls study (200 women in each arm) was conducted at Saad Abualila Maternity Hospital, Khartoum, Sudan.The cases were women with preeclampsia and the controls wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
1
16
1
Order By: Relevance
“…Preeclampsia (which is characterized by multilevel maternal endothelial dysfunction) may be triggered by or result from an imbalance between angiogenic, antiangiogenic, and proangiogenic factors, e.g., vascular endothelial growth factor [ 8 , 14 ]. Ahmed et al reported that women who were seropositive for HBsAg had a higher risk of preeclampsia compared with women who were seronegative for HBsAg [ 15 ]. Conversely, KLB R et al found no association between maternal HBV infection and preeclampsia [ 6 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Preeclampsia (which is characterized by multilevel maternal endothelial dysfunction) may be triggered by or result from an imbalance between angiogenic, antiangiogenic, and proangiogenic factors, e.g., vascular endothelial growth factor [ 8 , 14 ]. Ahmed et al reported that women who were seropositive for HBsAg had a higher risk of preeclampsia compared with women who were seronegative for HBsAg [ 15 ]. Conversely, KLB R et al found no association between maternal HBV infection and preeclampsia [ 6 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In multigravid women who attended ANC from the first trimester, there was no increased risk of miscarriage with HBV, which differs from recent previous reports [ 11 , 32 ]. Pregnancy associated morbidity (GDM, eclampsia and preeclampsia) and outcomes of stillbirth and PTB were also not significantly different by HBV status in this cohort [ 33 , 34 ]. Careful interpretation of obstetric outcomes is required due to the linear association of HBV infection with age and with age and gravidity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our study showed that an HBV infection during pregnancy increases the risk of ICP (1.1% vs. 0.2%, P < 0.05) and pre-eclampsia (3.4% vs. 2.5%, P < 0.05). These findings, which have rarely been investigated before, may have important clinical implications for pregnant women [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%